Analysing the Factors Affecting the Long-term Investment Intention of Investors - Sune Ferreira-Schenk; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2023)
The intention of investors to invest over a long term is generally aimed toward stable returns and low liquidity. The framework of this article looks at the theoretical concepts, investor characteristics and investor bias in a risk profile that could influence investors’ intent to invest over the long term. Based on traditional investment theory, investment companies acknowledge the impact of risk tolerance on the desired investment horizon of investors. However, traditional risk assessments are limited since they omit variables like personality measures and behavioural finance biases which could affect an investor’s long-term investment intentions. The unfavourable results might be less accurate investor profiles and an investment portfolio not meeting the required return objective. This study included a sample size of 593 private investors. The results indicated that personality traits (extraversion, openness to experience), risk tolerance, and behavioural biases (overconfidence bias) significantly influence long-term investment intentions. By incorporating the above-mentioned factors, financial planners and institutions can more accurately profile their clients and offer financial products that are more suitable for the investor’s needs.